Cavity preparation machine for the standardization of in vitro preparations - Carlos José Soares; Rodrigo Borges Fonseca; Henner Alberto Gomide; Lourenço Correr-Sobrinho (Sociedade Brasileira de Pesquisa Odontológica, 2008)
Several in vitro studies employ the confection of cavity preparations that are difficult to standardize by means of manual high speed handpieces. This study presents the development of a cavity preparation machine designed to standardize in vitro cavity preparations. A metal base of 25 mm x 25 mm x 4 mm (length x width x height) was coupled to a small mobile table which was designed to be able to move by means of two precision micrometers (0.01-mm accuracy) in the horizontal directions (right-left, and back-front). A high speed handpiece was coupled to a metallic connecting rod which had an accurate dial indicator enabling control of the vertical movement. The high speed handpiece is also able to move 180° around its longitudinal axis and 360° around its transversal axis. The suggested cavity preparation machine precisely helps in the standardization of cavity preparations for in vitro studies.